Pengaruh Disiplin Kerja, Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Tata Wisata Balikpapan - Anhar, Bani; Amanda, Nadya Dwi (Sekolah Tinggi Ilmu Ekonomi Balikpapan, 2025)
This study aims to provide empirical evidence regarding the influence of work discipline, work motivation, and job satisfaction on employee performance at PT. Tata Wisata Balikpapan. The type of research used is quantitative with a multiple linear regression analysis approach using the SPSS version 25 application. The population in this study were all employees of PT. Tata Wisata Balikpapan with a total of 47 respondents, and the sampling technique used was saturated sampling. The results of this study indicate that partially: (1) Work discipline has a positive and significant effect on employee performance with tcount 2.505 > ttable 1.681 and significance value of 0.016 < 0.05. (2) Work motivation has a positive and insignificant effect on employee performance with tcount 1.939 > ttable 1.681 and significance value of 0.059 > 0.05. (3) Job satisfaction does not have a negative and insignificant effect on employee performance with tcount -0.583 < ttable 1.681 and significance value of 0.563 > 0.05. (4) Simultaneously, work discipline, work motivation, and job satisfaction have a significant effect on employee performance with a calculated Fcount 5.149 > Ftable 3.21 and significance value of 0.004 < 0.05